American flintknappers : Stone Age art in the age of computers - Whittaker, John C. (John Charles), 1953- (University of Texas Press, 2004)
"Whittaker's American Flintknappers will be an important resource for students of modern replication studies. This publication not only presents information on modern non-academic flintknappers, it also addresses issues of interest to anyone studying folk technologies in general."--The Journal of the Royal Anthropological Institute "This is a superb book, authored by one of the only people with both the anthropological background and the connections in the world of contemporary flintknapping to write it. It really is unlike any work I'm aware of in lithics studies."--Michael Stafford, Director, Cranbrook Institute of Science Making arrowheads, blades, and other stone tools was once a survival skill and is still a craft practiced by thousands of flintknappers around the world. In the United States, knappers gather at regional "knap-ins" to socialize, exchange ideas and material, buy and sell both equipment and knapped art, and make stone tools in the company of others. In between these gatherings, the knapping community stays connected through newsletters and the Internet. In this book, avid knapper and professional anthropologist John Whittaker offers an insider's view of the knapping community. He explores why stone tools attract modern people and what making them means to those who pursue this art. He describes how new members are incorporated into the knapping community, how novices learn the techniques of knapping and find their roles within the group, how the community is structured, and how ethics, rules, and beliefs about knapping are developed and transmitted. He also explains how the practice of knapping relates to professional archaeology, the trade in modern replicas of stone tools, and the forgery of artifacts. Whittaker's book thus documents a fascinating subculture of American life and introduces the wider public to an ancient and still rewarding craft